2021
DOI: 10.1136/emermed-2021-211786
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of unrecognised endobronchial intubation in major trauma patients

Abstract: BackgroundEmergency tracheal intubation during major trauma resuscitation may be associated with unrecognised endobronchial intubation. The risk factors and outcomes associated with this issue have not previously been fully defined.MethodsWe retrospectively analysed adult patients admitted directly from the scene to the ED of a single level 1 trauma centre, who received either prehospital or ED tracheal intubation prior to initial whole-body CT from January 2008 to December 2019. Our objectives were to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Mortality rates at 24 h and at 30 days were similar in all groups. This is in line with results from 26 of 616 intubated adult trauma patients of our center [ 11 ]. However, we observed two cases of possibly unnecessary tube thoracostomy due to unrecognized endobronchial intubation [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mortality rates at 24 h and at 30 days were similar in all groups. This is in line with results from 26 of 616 intubated adult trauma patients of our center [ 11 ]. However, we observed two cases of possibly unnecessary tube thoracostomy due to unrecognized endobronchial intubation [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Tracheal intubation into one mainstem bronchus may cause impairment of gas exchange and lung atelectasis [ 10 ]. Furthermore, unrecognized endobronchial intubation may also lead to avoidable chest tube placement at the unventilated chest side due to absent breath sounds mimicking pneumothorax [ 11 , 12 ]. Although there is previous evidence that children are prone to endobronchial intubation, studies identifying associated factors are scarce [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 17 patients with no relevant chest injuries and chest tube placement before CT, more than half of them had issues with deep tracheal tube positions, which might have been the reason for chest tube placement. In a previous study, we found unrecognized endobronchial tube malposition detected on CT in 4.2% of the patients [ 25 ]. Seven of them received chest tube placement at the contralateral chest side, four of which were presumably because of the absence of breath sounds.…”
Section: Discussionmentioning
confidence: 99%
“…Deep placement can impact the carina, leading to hypertension, tachycardia, and bronchospasm ( Varshney et al, 2011 ). Moreover, endobronchial intubation, or unintended placement of the tube in the left or (more commonly) right main bronchi, can result in one-lung ventilation ( De Marchi, 2014 ; Lohser and Slinger, 2015 ; Heyne et al, 2022 ), causing injury to both lungs. The ventilated lung can suffer from tension pneumothorax ( Salem and Baraka, 2013 ) and reduced residual air ( Lohser and Slinger, 2015 ), while the unventilated lung may experience atelectasis, hypoxemia, and hypercapnia ( Lohser and Slinger, 2015 ).…”
Section: Methodsmentioning
confidence: 99%